Life and the Posthuman - McClellan, Serena Eva (Curtin University, 2021)
This thesis addresses the posthumanist problem of reconfiguring what and how the post/human means, rereading foundational binaries like human/nonhuman and life/nonlife as texts in themselves with a thickness that strains against the discursive structures that produce (and reduce) them as such. It attempts to petromorphically portray stone worlding without reverting to the assumed capacities of living (human) beings, suggesting a worlding that identifies the forces and intensities out of which “being,” stone and otherwise, emerges.